Automatic Monitoring System for Hydroponic Farming: IoT-Based Design and Development - Nguyen, Huu Cuong; Thi, Bich Thuy Vo; Ngo, Quang Hieu (Asian Journal of Agriculture and Rural Development, 2022)
Traditional agriculture is currently facing many difficulties and obstacles. One reason is that climate change has led to a harsher environment and more pests and diseases. Also, the expansion of industrial zones has significantly reduced the arable land area. To overcome these difficulties, farmers need to change their farming methods and apply scientific and technological advances to their practice. In this paper, we report on the design and development of an automatic monitoring system for hydroponic farming based on the internet of things technique. This system allows sensor data to be collected in real time. An IoT gateway and virtual server were developed to transmit this gathered data to the cloud and store it. Via the web interface, the user can observe all the sensor data of the environment and hydroponic solution, as well as control the farming equipment. The system has been tested and evaluated during lettuce growth in an NFT hydroponic system. The experimental results show that the proposed system operates stably and achieves high reliability. The collected sensor data stored on the server can be used to analyze and evaluate the impact of environmental parameters on plant growth during cultivation.